NFATc1 supports imiquimod-induced skin inflammation by suppressing IL-10 synthesis in B cells - Hani Alrefai; Khalid Muhammad; Ronald Rudolf; Duong Anh Thuy Pham; Stefan Klein-Hessling; Amiya K. Patra; Andris Avots; Valesca Bukur; Ugur Sahin; Stefan Tenzer; Matthias Goebeler; Andreas Kerstan; et al. (Nature Communications, 2016)
Regulatory B cells are important for preventing skin autoimmunity. Here the authors show that NFATc1 suppresses IL-10 transcription in regulatory B cells, and inhibiting NFATc1 decreases immunopathology in a mouse model of imiquimod-induced skin inflammation.